Design of liquid-crystalline gold nanoparticles by click chemistry - Mischler, Sylvain; Guerra, Sebastiano; Deschenaux, Robert (My University, 2012)
Mesomorphic alkyne-based first- and second-generation dendrons were grafted onto gold nanoparticles carrying azide groups under click reaction conditions. The nanoparticles decorated with the dendrons displayed liquid-crystalline properties and good thermal stability.